Hubungan Sikap Altruisme Konselor Sekolah dengan Minat Siswa Mengikuti Layanan Konseling Individu - wijayanti, amalia iman; awalya, awalya (Universitas Negeri Semarang, 2016)
The research was conducted based on the phenomenon that occurs in junior high school students who have a low interest in participating in individual counseling and implementation of counseling services performed poorly. The purpose of this study was to determine the attitude of altruism relationship counselor with the student's interest in participating in individual counseling. The research is a survey research, research sites in SMP Bobotsari. Data collection methods used were Psychological Scale. Data were analyzed using Pearson product moment correlation. The results showed the attitude of altruism relationship counselor with the student's interest in participating in individual counseling classes VIII to the value of